Kajian Etika Hindu Pada Usaha Pelestarian Danau Batur Di Desa Buahan Kecamatan Kintamani Kabupaten Bangli - Somawati, Ayu Veronika; Relin DE; Alit Putrawan, I Nyoman (Jurnal Penelitian Agama Hindu, 2024)
Buahan Village, as one of the villages on the outskirts of Lake Batur, since old time has local wisdom that has positive implications for the sustainability of Lake Batur. This research aims to examine local wisdom so that the ancestral heritage can be understood and implemented in daily life, so the preservation of the lake can be maintained. The type of qualitative descriptive research using observation methods, in-depth interviews and analysis of various relevant literature was used in this research. Based on the research results, it shows that the community in Buahan Village is making efforts to preserve Lake Batur through local wisdom, including through the establishment and preservation of sacred buildings as the sthana of Ida Bhatari Dewi Danuh who is believed to be the owner of Lake Batur. Buahan Village also has regulations on the use of lake borders which are still implemented today so that if you look at the conditions around, the border area of Buahan Village has very few buildings compared to other villages around Lake Batur. The preservation efforts carried out by the community have had positive implications for the lives of the people, both from a spiritual, intellectual and emotional perspective. This research draws the conclusion that the efforts to preserve Lake Batur carried out by the community in Buahan Village are indirectly a form of self-realization that humans are part of an ecological community that cannot possibly live without nature, so nature really needs to be preserved.